Globalization and Coerced Labour in Early Modern Asia and Africa - Dalrymple-Smith, Angus; van Rossum, Matthias (Comparativ, 2021)
Early modern globalization was accompanied with a simultaneous expansion of systems of coerced labour exploitation across the globe. This article seeks to deepen our understanding of the impact of early globalization by using a comparative approach to examine the effects of the increasing global demand for (coerced) labour on systems of bondage and slavery, especially in West Africa and South Asia. We argue that the developing systems of globalized trade during the early modern era had a transformative impact on many local forms of slavery and bondage in Africa and Asia by connecting them to global demands for closed, commodified (or ‘chattel’) slavery. We conclude that that local systems of slavery and bondage and global systems of commodified slavery were not separate and unconnected, but co-existed and interacted at three levels: that of state formation and expansion; the adaption of socio-political systems to increase slave exports in response to the demands of a globalized labour market; and the modification of local systems of slave and bonded labour. This underlines the need for new global-comparative approaches to deepen our understanding of the coercive roots of global capitalism and the long-term transformations of slavery.